The Positive Thinking and its Relationship to The job Satisfaction Afield study among sample of post graduate Classroom Teachers in the Schools of Latakia - Sakkor, Sam; Hawat , Dima (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aims to identify the relationship between the positive thinking and the job satisfaction among teachers ( post graduate classroom teachers) in the schools of Latakia, and to know the impact of the variables of gender, and number of years in service on the nature of the research sample responses, and in order to achieve the objectives of the research descriptive approach were used, through a positive thinking of preparation scale ( Angram and Whiskney) (1994), and a job satisfaction scale ( prepared by researcher), and a sample of (177) teachers, and the most important results: - Pattern prevailing thinking among teachers ( post graduate classroom teachers) in the schools of Latakia, is positive. - The level of job satisfaction among teachers ( post graduate classroom teachers) in the schools of Latakia, is moderate, and interns of importance ,the direction field came at first, in addition, the physical and moral motivations come at last . - The existence of appositive correlation statistically significant between the positive thinking and the job satisfaction. - The variable of gender affects on the nature of the sample responses to each of the positive thinking and total score on the scale of job satisfaction, the differences came in favor of females. - The variable of number of years in service( from five to ten years ) affects on the nature of the sample responses on the scale of the positive thinking . and on the job satisfaction, this effect is for the most number of years in service.